EKSTRAKSI LIMBAH KULIT JERUK PAHIT (CIRTUS AURANTIUM) DENGAN VARIASI PROSES PERENDAMAN DAN DAYA MICROWAFE MENGGUNAKAN METODE MICROWAVE ASSISTED EXTRACTION (MAE) - Ihza Zaki Safari; Muyassaroh (Teknik Kimia ITN Malang, 2024)
Essential oil, also known as etheric oil (Aetheric Oil), is a volatile compound widely utilized in various industries, including pharmaceuticals, cosmetics, and aromatherapy. In this study, the main material used is orange peel (Citrus aurantium), which is extracted into essential oil using the Microwave-Assisted Extraction (MAE) method. The study aims to obtain a high essential oil yield with optimal quality. The variations in microwave power used include 100 W, 150 W, 200 W, 280 W, and 399 W, with soaking durations of 3, 4, and 5 days. Various parameters were analyzed to assess the quality of the obtained essential oil, including organoleptic tests (color), yield, refractive index, density measurement, and analysis using Gas Chromatography-Mass Spectrometry (GC-MS). The results indicate that the optimal condition was achieved at a microwave power of 280 W with a soaking duration of 5 days. Under these conditions, the essential oil yield was relatively high, with a refractive index of 1.040 and a density of 1.039. The obtained essential oil had a dark yellow color, indicating good quality. GC-MS analysis revealed that limonene, the main component of orange essential oil, was detected at 1.30% at a retention time of 3.675 minutes, followed by 1.80% at a retention time of 4.240 minutes, and 0.28% at a retention time of 12.750 minutes. Based on these findings, the MAE method proved effective in extracting essential oil from orange peel, particularly under optimal power and soaking conditions. This study provides further insights into efficient extraction techniques for producing high-quality essential oils.